Graceful labelling of some 3-distant trees - Panigrahi, Pratima (Utilitas Mathematica, 2010)
In this paper we first construct some graceful diameter six trees. Then by applying component moving transformation to these diameter six trees we give graceful labelling to several 3-distant trees.